Association Between Maternal Undernutrition and Pre‐Labor Rupture of Membranes in Ethiopia: A Systematic Review and Meta‐Analysis of Observational Studies - Ebrahim Msaye Assefa; Hussen Abdu; Altaseb Beyene Kassaw; Mekonnen Belete; Amare Abera Tareke; Addis Alem; Mohammed Derso Bihonegn; Abdulaziz Kebede Kassaw; Ahmed Juhar Temam; Gashaw Abebe; Melese Shenkut Abebe; Gosa Mankelkl; et al. (Health Science Reports)
ABSTRACT Background and Aims In Ethiopia, pre‐labor rupture of membranes impacts maternal and perinatal health, while maternal undernutrition remains a major public health issue. The findings of previous studies have been inconsistent, and no nationwide pooled data exist. Therefore, this review aims to investigate the association between maternal undernutrition and pre‐labor rupture of membranes in Ethiopia. Methods Comprehensive and systematic searches were conducted across various databases, including PubMed, Google Scholar, Hinari, and ScienceDirect. The data were extracted using Microsoft Excel and analyzed with STATA version 17. The risk of bias and certainty of the evidence were evaluated. Heterogeneity was assessed using I2 statistics, and a random effects model was employed to estimate the pooled effect size (odds ratio) with a 95% CI. A funnel plot and Egger's test were also used to assess potential publication bias. Results A total of twelve observational studies, involving 4016 participants, were included in this systematic review and meta‐analysis. Most studies showed a low risk of bias and a moderate level of certainty in the evidence. The pooled results indicated a significant association between maternal undernutrition and pre‐labor rupture of membranes in Ethiopia (pooled OR = 3.24; 95% CI: 2.08–5.06), with substantial heterogeneity (I2 = 74.9%, p < 0.001). Sensitivity analysis confirmed the stability of the pooled estimates, and no publication bias was detected. Conclusion This meta‐analysis shows a significant association between maternal undernutrition and an increased risk of pre‐labor rupture of membranes in Ethiopia. Therefore, health institutions should assess the nutritional status of pregnant women during prenatal visits for counseling and supplementation programs. Policymakers need to develop public health policies to address maternal nutrition. We recommend further research that explore the role of specific nutrient deficiencies in pre‐labor rupture of membranes. Review Registration ID PROSPERO CRD42024579002.